Demand and supply side factors that drive delayed referrals from traditional birth attendants to public primary healthcare facilities: Insights from three states in Nigeria. - Chinelo Ifeoma Okeke; Prince Agwu; Enyi Etiaba; Obinna Onwujekwe (PLOS Global Public Health)
Despite global efforts encouraging institutional deliveries with skilled attendants, many pregnant women in developing countries such as Nigeria continue to rely on traditional birth attendants (TBAs) for child delivery. Attempts at weeding off TBAs have been firmly resisted by their clients who have developed confidence and trust in their services and herald them as first and trusted responders to child delivery cases. Unfortunately, recent evidence has shown that TBAs in servicing public trust and for other reasons, often do not timely refer their clients to the closest source of formal healthcare-primary healthcare centres (PHCs). Looking into the motivations for these reasons is the crux of the current study. Data were collected through qualitative interviews with 85 respondents across three states in Nigeria. The qualitative data comprised of 73 in-depth interviews and 12 focus group discussions. Respondents were TBAs and other informal health providers, formal health workers, policymakers, community leaders and service users. Data were analysed thematically to explore the demand and supply determinants of referrals from TBAs to the formal healthcare providers. Demand side factors that constrain referrals from TBAs to PHCs were community preference for TBAs, and cultural and religious inclinations of the consumers to TBAs' practices of infusing religious teachings and rules into the process of child delivery. Supply-side factors were infrastructural deficits, staff shortages and lack of sanctions for poor practices in PHCs. Demand and supply-side factors constrain the referral of pregnant women from TBAs to the PHC facility for child delivery. These factors should be addressed, and innovative interventions used to link the TBAs to the formal health system for increased institutional deliveries with skilled birth attendants. The interventions could include incentives to TBAs to encourage early referrals.